Evolutionary legacy of a forest plantation tree species (Pinus armandii): Implications for widespread afforestation - Yun Jia; Richard I. Milne; Juan Zhu; Lian‐Ming Gao; Guang‐Fu Zhu; Gui‐Fang Zhao; Jie Liu; Zhong‐Hu Li (Evolutionary Applications, 2020)
Abstract Many natural systems are subject to profound and persistent anthropogenic influence. Human‐induced gene movement through afforestation and the selective transportation of genotypes might enhance the potential for intraspecific hybridization, which could lead to outbreeding depression. However, the evolutionary legacy of afforestation on the spatial genetic structure of forest tree species has barely been investigated. To do this properly, the effects of anthropogenic and natural processes must be examined simultaneously. A multidisciplinary approach, integrating phylogeography, population genetics, species distribution modeling, and niche divergence would permit evaluation of potential anthropogenic impacts, such as mass planting near‐native material. Here, these approaches were applied to Pinus armandii, a Chinese endemic coniferous tree species, that has been mass planted across its native range. Population genetic analyses showed that natural populations of P. armandii comprised three lineages that diverged around the late Miocene, during a period of massive uplifts of the Hengduan Mountains, and intensification of Asian Summer Monsoon. Only limited gene flow was detected between lineages, indicating that each largely maintained is genetic integrity. Moreover, most or all planted populations were found to have been sourced within the same region, minimizing disruption of large‐scale spatial genetic structure within P. armandii. This might be because each of the three lineages had a distinct climatic niche, according to ecological niche modeling and niche divergence tests. The current study provides empirical genetic and ecological evidence for the site‐species matching principle in forestry and will be useful to manage restoration efforts by identifying suitable areas and climates for introducing and planting new forests. Our results also highlight the urgent need to evaluate the genetic impacts of large‐scale afforestation in other native tree species.